CHALCONE CONTENT IN THE ETHANOL EXTRACT OF ANGELICA KEISKEI LEAVES BY SPECTROPHOTOMETRIC METHOD - Zain, Dichy Nuryadin (Journal of Pharmacopolium, 2019)
Angelica keiskei Koidzumi, known as ashitaba or Japanese celery, has been the focus of interest in Asia. Thisplant has been reported to possess antituberculosis activity against Mtb H37Rv and antioxidant activity equals tovitamin E. It was predicted that those activities were caused by the plant?s secondary metabolites, e.g.flavonoids and polyphenols. Xanthoangelol (XAG) and 4-hydroxyderricin (4-HD), two chalcones orchalconoids (flavonoids with an open C-ring), are contained in the stems of A. keiskei. This work was aimed todetermine the chalcone level, calculated as XAG, in the leaves of A. keiskei planted in Mount Rinjani, Lombokisland, Indonesia. The plant was taxonomically identified at Herbarium Bandungense, Bandung Institute ofTechnology, Indonesia. The leaves were extracted using ethanol 70% and were screened for its phytochemicalcontents. The determination of the chalcones was carried out by employing standard addition UVspectrophotometric method. Results indicated that phenols, flavonoids, alkaloids, tannins and saponins werecontained in both the dried leaves and the leaves extract. The chalcones, calculated as XAG, were 1.959% w/w.